2019
DOI: 10.1016/j.nima.2019.06.025
|View full text |Cite
|
Sign up to set email alerts
|

Density changes in low pressure gas targets for electron scattering experiments

Abstract: A system of modular sealed gas target cells has been developed for use in electron scattering experiments at the Thomas Jefferson National Accelerator Facility (Jefferson Lab). This system was initially developed to complete the MARATHON experiment which required, among other species, tritium as a target material. Thus far, the cells have been loaded with the gas species 3 H, 3 He, 2 H, 1 H and 40 Ar and operated in nominal beam currents of up to 22.5 µA in Jefferson Lab's Hall A. While the gas density of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…The experiment employed a set of solid targetsaluminum, carbon (single foil and a multi-foil composed of 9 foils), and titanium-as well as a closed cell of gaseous argon [13]. The aluminum target consisted of two identical foils of the 7075 alloy, the thickness of which was 0.889 ± 0.002 g/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The experiment employed a set of solid targetsaluminum, carbon (single foil and a multi-foil composed of 9 foils), and titanium-as well as a closed cell of gaseous argon [13]. The aluminum target consisted of two identical foils of the 7075 alloy, the thickness of which was 0.889 ± 0.002 g/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…The yields are normalized such that ( , ′ ) A (0 A) = 1. Additional information on the determination of these corrections, including the event-selection criteria, check of the methodology on a solid target, efficiency studies, and other details can be found in [109]. The corrections used in this analysis for the different gas targets at = 22.5 A are shown in Table 3.6.…”
Section: Density ('Boiling') Correctionsmentioning
confidence: 99%
“…The thickness is obtained by multiplying the gas density [mg/cm 3 ] by the target length (25 cm). See[107,109,110] for details.…”
mentioning
confidence: 99%
“…The experiment ran in 2018 in Hall A of the Thomas Jefferson National Accelerator Facility. It used the two highresolution spectrometers (HRSs) [23] and a 20 μA electron beam at 4.326 GeV incident on one of four identical 25-cmlong gas target cells filled with hydrogen (70.8AE0.4mg=cm 2 ), deuterium (142.2 AE 0.8 mg=cm 2 ), helium-3 (53.4AE 0.6 mg=cm 2 ), and tritium (85.1 AE 0.8 mg=cm 2 ) [24]. To minimize systematic uncertainties between measurements, the HRS were not moved when changing among the targets, which were installed on a linear motion target ladder.…”
mentioning
confidence: 99%
“…where C is the total accumulated beam charge, t is the live time fraction in which the detectors are able to collect data, A ¼ 3 is the target atomic mass, ρ is the nominal areal density of the gas in the target cell, and b is a correction factor to account for changes in the target density caused by local beam heating. b was determined by measuring the beam current dependence of the inclusive event yield [24]. V B is a factor that accounts for the detection phase space and acceptance correction for the given ðp miss ; E miss Þ bin and C Rad and C BM are the radiative and bin migration corrections, respectively.…”
mentioning
confidence: 99%